Reliability of the adapted compensatory arm and leg movements scale during perturbation treadmill walking in older adults - Schwenk, Michael; Ramirez Mantilla, Mitzi; Schmidt, Nina Marie; Haug, Vanessa; Werner, Christian; Gruber, Markus; Denkinger, Michael; Fleiner, Tim (Frontiers in Sports and Active Living, 2025)
IntroductionReactive balance during walking is crucial for fall prevention, as it determines recovery from unexpected perturbations like slips and trips. Existing reactive balance assessments are complex and lab-based, lacking an easy-to-use alternative for broader application in clinical environments. The Adapted Compensatory Arm and Leg Movements (A-CALM) scale was developed to address this gap by providing an observer-based tool to evaluate compensatory balance reactions during perturbation treadmill walking. This study assessed its inter- and intra-rater reliability in fall-prone older adults.MethodsEighteen participants aged 82 ± 7 years walked on the BalanceTutor® perturbation treadmill. Depending on assigned intensity levels, each received 8, 16, or 24 perturbations in mediolateral and anteroposterior directions. Compensatory balance reactions after each perturbation were video-recorded and evaluated by three trained raters using the A-CALM scale, capturing responses from minor adjustments to near-fall scenarios. Arm movements were rated on a five-point scale (1 = near fall, 5 = regular arm swing), while leg movements were rated on an eight-point scale (1 = near fall, 8 = normal walking), with intermediate scores reflecting varying recovery steps. Inter-rater reliability was assessed using Fleiss' Kappa, while intra-rater reliability over a two-week interval was evaluated using Cohen's Kappa.ResultsOverall, 288 perturbations were recorded. The A-CALM scale demonstrated strong intra-rater reliability, with Kappa values of 0.85 (95% CI = 0.80–0.89) for arm scores, 0.80 (95% CI = 0.75–0.86) for leg scores, and 0.86 (95% CI = 0.83–0.90) for total scores, indicating a high level of consistency in the raters' assessments across time. Inter-rater reliability was substantial for arm scores (K = 0.67, 95% CI = 0.62–0.72) but moderate for leg scores (K = 0.48, 95% CI = 0.44–0.51) and total scores (K = 0.41, 95% CI = 0.38–0.44) with significant values in all analyses (p < 0.001).ConclusionThe A-CALM scale showed high intra-rater consistency and moderate-to-substantial inter-rater agreement, with greater reliability for arm than leg movements. Single-rater use is recommended to enhance stability, while future work should refine leg scoring and validate the scale in larger cohorts with outcomes like falls and functional decline.